Single molecule distribution of RhD binding epitopes on ultraflat erythrocyte ghosts. Issue 43 (29th October 2020) - Stainer, Sarah; Reisetbauer, Sara; Ahiable, Joan E. A.; Ebner, Leon; Zhu, Rong; Reindl, Dagmar; Körmöczi, Günther F.; Ebner, Andreas
Abstract : The Rh blood group system plays a key role in transfusion and organ transplant medicine. AFM-based recognition imaging on ulraflat erythrocyte ghost makes it possible to determine the molecular distribution of Rh epitopes over the entire erythrocyte. Abstract : The Rh blood group system plays a key role in transfusion and organ transplant medicine. The complex transmembrane Rh polypeptides RhD and RhCE carry numerous antigens, including the extremely immunogenic D antigen. The Rh polypeptides form multimolecular Rh complexes with certain transmembrane and skeletal proteins, with so far only incompletely understood physiological functions. Determination of the energy landscape of individual Rh binding epitopes towards their specific interaction partners as well as their localization across the red blood cell (RBC) membrane requires single molecule approaches including large area high resolution recognition imaging. Atomic force microscopy based molecular recognition force spectroscopy in combination with single molecule recognition imaging fulfills these requirements. For unbiased single molecule results, nano-mechanical influences due to cell elasticity have to be eliminated. This is realized by generation of ultra flat erythrocyte ghosts on a solid support. We developed a protocol for the preparation of complete ultraflat erythrocyte ghosts and determined the molecular binding behaviour of different anti-D antibodies towards their binding epitopes on RhD positive and negative erythrocytes. Performing optimized topography and recognition imaging at 16 Mpixel resolution allowed localisation of individual RhD molecules at the single molecule level across an entire RBC. A map of Rh antigens across integer ultraflat RBC ghosts was generated with nanometer resolution. Here we show a homogeneous distribution on rim and dimple regions with comparable receptor densities. Furthermore, differences in the energy landscape between specific monoclonal antibodies were determined at the single molecule level.